Comparison of Sidenuk Nuclear Rice Agribusiness with Ciliwung Rice in Bajeng District, Gowa Regency - Amiruddin, Achmad; Heliawaty; Salsabilah, Devita Tasha; Bate, Andi Muhammad Farid Fausan; Ardiyanto, Anang Nur (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2023)
This study aims to analyze the comparison of production input use, production process, marketing, support, and income of rice fields planted with Sidenuk nuclear rice and rice fields planted with Ciliwung rice in Bajeng District, Gowa Regency. The data obtained were analyzed using the descriptive comparative method to compare the comparative use of production inputs, production processes, marketing, support and farm income, and using comparative test analysis using the t-test to compare differences in income between Sidenuk Nuclear rice farmers and Ciliwung rice farmers. There are differences in agricultural inputs in this study, the difference is the area of land, the type and amount of seeds used, the type and amount of fertilizer used, the type and amount of pest and plant disease drugs used, as well as the amount of labor and the length of work required. In the production section, there are differences in seeding time, transplanting time, the amount and time of weeding, fertilizer time, and harvest time. In the marketing and support section, no differences were found. T test results sig value, (2-tailed) of 0.000 <0.05 which means H0 is rejected so it can be concluded that there is a significant difference between the net income of Nuclear Sidenuk rice farmers and Ciliwung rice farmers in Bajeng district, Gowa Regency.